The utility of anatomy assessment in preclinical undergraduate medical curricula: a scoping review - Woon, Choy Ker; Wong, Kah Hui; Alias, Aspalilah; Abas, Razif; Hadie, Siti Nurma Hanim (John Wiley and Sons Inc, 2025)
Anatomy assessments are crucial for developing critical thinking and analytical skills in preclinical undergraduate medical curricula. However, because there is little published empirical evidence, the value of anatomy assessment remains largely unexplored. The aim of this scoping review, conducted in accordance with the Joanna Briggs Institute (JBI) scoping review guidelines, was to explore the utility elements adopted in anatomy assessment within preclinical undergraduate medical curricula. A rigorous three-step search approach across five electronic databases (Scopus, WoS, PubMED, Wiley Online, and EBSCOHost) generated an initial pool of 721 records, which were assessed for duplication and eligibility, leading to the inclusion of 43 records from which data were extracted. The extracted data covered various utility elements of anatomy assessment including validity, reliability, practicality, feasibility, cost-effectiveness, and educational impact, along with various assessment contexts such as assessed competencies, assessment function, and assessment tools. The findings indicate a strong emphasis on assessing cognitive competencies in anatomy education; psychomotor and affective competencies received less attention. Identified gaps include limited exploration of validity evidence, assessment methods, cost-effectiveness, and educational impact of assessment. Moreover, the study highlights challenges in implementing formative assessments alongside summative assessments, constraints in assessing psychomotor skills, and the subjective nature of assessing affective competencies. By addressing these gaps and leveraging innovative assessment tools and practices, educators can enhance the quality of anatomy education and prepare students better for their future careers in medicine.